Influence of Installation Orientation and Cone Angle on Pressure Drop and Filtration Efficiency of Conical Strainers - Amnur Akhyan; Mhd Dhowiy Hussein; Mohd Azahari Bin Razali (Scientific Contributions Oil and Gas, 2025)
Cone strainers are very important in oil and gas pipeline systems because they prevent particles from entering the system and damaging pumps, compressors, and other critical equipment. This study experimentally examines the effects of cone angle, installation orientation, and open area ratio (OAR) on pressure drop (ΔP) and filtration efficiency (η) in conical filters. Four setups were examined with cone angles of 74° and 81° and hole diameters of 4 mm and 6 mm, at flow rates between 15 to 30 m³/hour. The results reveal that the 81° configuration (OAR = 38%) with unidirectional installation has the lowest pressure drop (1,250–2,500 Pa) and a filtration efficiency of over 92%, making it ideal for energy-efficient use. Conversely, the 74° cone can capture more particles (>93%) but experiences higher pressure loss (up to 9,500 Pa), making it suitable for applications requiring very stringent filtering. Installing the counter-current way was shown to increase turbulence and lower efficiency by up to 20%, which demonstrates the importance of the correct installation orientation for maintaining hydrodynamic stability and filtering effectiveness. These results highlight the critical need to optimise cone geometry and OAR to strike a balance between energy efficiency, hydraulic stability, and filtering performance. For pre-filtration and equipment protection in oil and gas systems, the optimal setup is an 81° angle, a 6 mm hole, a 38% OAR, and unidirectional flow. This configuration can contribute to smoother operations, energy savings, and reduced maintenance requirements.